Effect of density and resistivity measurement for foam flooding propagation in static condition - Irawan, S. (Institute of Physics Publishing, 2017)
Foam flooding is one of the method that is currently used to optimize the amount of oil in sub surface. Foam flooding is used to overcome the weakness of water injection, gas injection, and water alternating gas injection. Foam is the mixture of gas, water and surfactant. Foam propagation plays an important part in porous medium, foam propagation is related to intrinsic properties of the fluids such as density and viscosity. Resistivity of the fluids should be taken also because in the end of the experiment, method that is used to track foam propagation in porous medium is resistivity measurement. The objectives of this experiment are to obtain fluid characterization and to understand the phenomena that is possibly occurred during foam injection in porous medium, specifically, to obtain the correlation between density and resistivity measurement. Foam is generated with several concentration of solutions which are various concentration of brine, various concentration of MFOMAX, oil, and distilled water. Several tests should be taken to observe the intrinsic properties of the fluids such as density test, viscosity test, resistivity and conductivity test. Based on the experiment, correlation between density of brine and brine concentration towards resistivity is inversely proportional. Correlation between density of fluid mix with MFOMAX and MFOMAX concentration towards resistivity is proportional. © Published under licence by IOP Publishing Ltd.